Solving time-varying mesh stiffness of spur gears based on improved potential energy method - Zhang, Hao; Zhang, Hongyuan (Journal of Mechanical Engineering Automation and Control Systems, 2024)
Meshing stiffness is an important factor in gear dynamics analysis. At present, there are many ways to calculate the meshing stiffness of gears, and we usually use the potential energy method to solve and calculate the meshing stiffness of healthy (faulty) gears. In this paper, the potential energy method, the improved potential energy method and the theoretical calculation method are used to solve the time-varying stiffness of the healthy spur gear pair, and the solution results are compared, which verifies the feasibility of the improved potential energy method to solve the gear meshing stiffness.